2014
DOI: 10.1186/1471-2407-14-747
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside promotes apoptosis by regulating HIPK2–p53 signaling in human colorectal cancer

Abstract: BackgroundWe investigated the role of the HIPK2–p53 signaling pathway in tumorigenesis and resistance to the drug Verbascoside (VB) in colorectal cancer (CRC), using in vivo and in vitro experiments.MethodsPrimary human CRC samples and normal intestinal tissues from patients were analyzed for HIPK2 expression by immunohistochemistry (IHC) and its expression was correlated against patients’ clinicopathological characteristics. Human CRC HCT-116 cells were implanted in BALB/c nude mice; mice with xenografted tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…Reportedly, Verbascoside is regulated in different organ cells, including Verbascoside promoted apoptosis via p53 in human CRC cells. 27 Furthermore reported that Verbascoside attenuates LPS-induced pro-inflammatory mediator production via TAK-1/JNK/AP-1 signalling in U937 cells. 37 Therefore, the role of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, Verbascoside is regulated in different organ cells, including Verbascoside promoted apoptosis via p53 in human CRC cells. 27 Furthermore reported that Verbascoside attenuates LPS-induced pro-inflammatory mediator production via TAK-1/JNK/AP-1 signalling in U937 cells. 37 Therefore, the role of…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] More importantly, Verbascoside also demonstrated various biological properties including anti-hepatotoxic, antinflammatory, anti-nociceptive, antioxidant and antihemolytic effects and antineoplastic properties in addition to numerous woundhealing and neuroprotective properties. 17,19,20,[22][23][24][25][26][27][28][29][30][31][32] However, literature no survey supporting the therapeutic effects of Verbascoside in treatment of renal fibrosis.…”
mentioning
confidence: 99%
“…Among the initial 39 hit compounds, five compounds such as haematoxylin, verbascoside, menadione, lithospermic acid and DITMD, showed a robust sigmoidal inhibitory dose response with an IC 50 ranging from 1.4 to 2.8 µM which were as active as purpurogallin (2.6±0.3 µM). It has been reported that haematoxylin, verbascoside, menadione and lithospermic acid possess anticancer activities such as anti-tumor action in mice, 25) promotion of apoptosis in human colorectal cancer, 26) induction of tumor tissue necrosis against pancreatic cancer, 27) and cytotoxic activity on human breast cancer cells, 28) respectively. The pharmacological information of DITMD has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TMZ administration adjuvant to radiotherapy might promote the elimination of glioblastoma stem cells and consequently prolong the survival of patients and has been used as first-line treatment for glioblastoma patients [8,9]. Verbascoside (VB) is a cancer therapeutic for colorectal cancer, glioma, and breast cancer [10]. Herein, TMZ was enrolled in the present study as a comparator with the function of VB.…”
Section: Introductionmentioning
confidence: 99%
“…VB is a component of Cistanche (a medical plant in traditional Chinese medical science) in the form of polyphenols, and it has high antioxidant power, which is inhibitory to cell proliferation and facilitated cell apoptosis in treating colorectal cancer via the homeodomain interacting protein kinase 2-p53 signaling pathway [10,12]. Inactivation of tumor suppressor phosphatases is known as a critical event in the pathogenesis of brain tumor glioblastoma [13].…”
Section: Introductionmentioning
confidence: 99%